If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 = 3x + -21 Reorder the terms: -3 + 5x = 3x + -21 Reorder the terms: -3 + 5x = -21 + 3x Solving -3 + 5x = -21 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -3 + 5x + -3x = -21 + 3x + -3x Combine like terms: 5x + -3x = 2x -3 + 2x = -21 + 3x + -3x Combine like terms: 3x + -3x = 0 -3 + 2x = -21 + 0 -3 + 2x = -21 Add '3' to each side of the equation. -3 + 3 + 2x = -21 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = -21 + 3 2x = -21 + 3 Combine like terms: -21 + 3 = -18 2x = -18 Divide each side by '2'. x = -9 Simplifying x = -9
| 49=-7t+(-7) | | 9m-5m+2=4m+2 | | X^2-6X-12X=0 | | 3y=-21+7x | | 2(x+1)(x+4)-(x-2)(x-2)=0 | | 6x+12-8x=20 | | 3*(x+2)-x= | | 15=3(5x+5) | | 12mn+4m+8mn+6m= | | (n-2)180= | | 2v^2+v+64=0 | | -4-4x+2x=-10 | | 1+4x=-31 | | a+-0.4=-3 | | 6(1+3d)=-8(-2m+5)-4 | | -3(4t-2)+7t=4t-4 | | 6x-27=4x+12 | | cx+5=dx-3 | | 5+2(x+1)=2n | | 9y+13=30 | | w^2-11=2-5w^2 | | 6x+40=8x-20 | | 5*x+2=11-x*8 | | 4b-8=1+6-3b-1 | | 2x^2+kx^2-2kx-16=0 | | 2x-(x+2)=2x-0.1 | | 6=7x-x+6 | | w*w+9=6w | | 4x+172=180 | | .3T-2.1C-2.3=7.6 | | 5r+4=9(r-3) | | (m/2)-(1/m)=(6m+5/12) |